Pemanfaatan air botani dari buah salak pondoh (Salacca zalacca var pondoh) untuk pembuatan roti tawar sourdough - Monika Rahardjo; Monang Sihombing (Program Studi Ilmu dan Teknologi Pangan, Universitas Yudharta, Pasuruan, 2023)
Indonesia has variety of fruits that have the potential to be used as botanical water in sourdough bread making, especially those with high sugar content. Salak pondoh (Salacca zalacca var pondoh) is one of Indonesia's native fruits that has a distinctive flavor and is favored by the public. This research aims to utilize botanical water from salak pondoh in the making of sourdough bread. This research method consists of several stages, namely making botanical water, making starter, evaluating yeast activity, and white bread production. The analysis performed on white bread includes physical analysis, chemical analysis, and sensory analysis. Yeast activity in this study showed that the use of sourdough starter with the percentage of 30% had the highest activity level of 1.035 ± 0.002 ml/hour. Proximate test results showed significant differences in protein content, water content, and fiber content, while carbohydrate, fat, and ash content were not significantly different. The results of the texture test showed significant differences for hardness and springiness parameters, while for other texture parameters there were no significant differences. Overall, white bread using sourdough starter from salak pondoh can develop well and can be accepted like white bread in general, even in this study white bread with the addition of sourdough starter obtained a higher hedonic rating compared to white bread sample control.